2021
DOI: 10.1186/s12904-021-00806-2
|View full text |Cite
|
Sign up to set email alerts
|

Before the 2020 Pandemic: an observational study exploring public knowledge, attitudes, plans, and preferences towards death and end of life care in Wales

Abstract: Background Understanding public attitudes towards death and dying is important to inform public policies around End of Life Care (EoLC). We studied the public attitudes towards death and dying in Wales. Methods An online survey was conducted in 2018. Social media and the HealthWiseWales platform were used to recruit participants. Data were analysed using descriptive statistics and thematic analysis. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Moreover, this talk signaled participants’ relational identities and desires not only for a particular kind of (holistic, non-medical) care but for particular caring relations, before and after a death, supporting a broad conceptualization of ‘care’. Such findings are further supported by a 2018 Welsh survey, 44 which found that being at home at the end of life was less important to respondents than being surrounded by loved ones.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, this talk signaled participants’ relational identities and desires not only for a particular kind of (holistic, non-medical) care but for particular caring relations, before and after a death, supporting a broad conceptualization of ‘care’. Such findings are further supported by a 2018 Welsh survey, 44 which found that being at home at the end of life was less important to respondents than being surrounded by loved ones.…”
Section: Discussionmentioning
confidence: 63%
“…Finally, our findings suggest a need to build public awareness about and access to hospices and in-patient palliative care, with journalists, clinicians, and not-for-profit organizations continuing to communicate these options. 44…”
Section: Discussionmentioning
confidence: 99%
“…Previous research identifies several barriers including lack of knowledge of the death system [ 51 ], fear/distress associated with thinking about death and dying [ 52 ] and difficulty engaging others in death talk or fear of upsetting others [ 53 ]. An aligned Welsh study [ 47 ] conducted at a similar period of time to the current study identified several levels of barriers, including social perception and practice (e.g. death as a societal ‘taboo’), lack of opportunities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel barriers to talking about death and dying were also identified, including a focus on interpersonal communication skills and cultural beliefs. The identification of facilitators to provide a more multi-dimensional understanding of the drivers of this behaviour was also a novel contribution of this study, with a previous lack of prior attention in the research literature [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation